PERCEPATAN INVOLUSI UTERI MELALUI MOBILISASI DINI PADA IBU POST PARTUM - Yunifitri, Astri; Aulia, Devy Lestari Nurul; Roza, Nova (Universitas Batam, 2021)
Post partum mothers experience uterine involution, where the uterine muscles contractso that the blood vessels that are open due to the attachment of the placenta willpinched, so that postpartum hemorrhage can be prevented. Early mobilization is very importantperformed on post partum mothers to accelerate the decrease in uterine fundal height. The purpose of this study was to determine the relationship between early mobilization and uterine involution. This research uses a qualitative approach (library research) with a literature study research method or literature. The results of all articles found that early mobilization provides benefits to postpartum mothers who can help the process of uterine involution after childbirth. Early mobilization has an effect on uterine involution in post partum mothers. Early mobilization can also restore body organs such as before pregnancy, expedite blood and placental remnants so that it can accelerate the decrease in TFU.